Survey of text mining clustering, classification, and retrieval - Berry Michael W (New York Springer-Verlag, 2004)
Many clustering methods are described hin this book. Most can be seen to have some degree of subjectivity, in defining what ends up in a given cluster. Or whether a cluster even exists or not. The analysis of Web documents forms a major portion of the bo
Several of the invited and contributed papers presented at the Text Mining Workshop held on April 13, 2002 in Arlington, VA have been compiled and expanded for this volume
Keywords: Cluster analysis; Data mining; Discriminant analysis